Uji Cemaran Bakteri pada Bawang Putih Giling yang Dijual di Pasar Tradisional Kecamatan Galang - Listrahot Tondang; Abdul Karim; Sartini Sartini (Universitas Medan Area, 2020)
Garlic is one of the spices or spices that has a delicious tastes and aroma and garlic has many health benefits. The ingredients purchased in the traditional market need to be kept clean to avoid bacterial contamination that cause disease. The study aims to determine bacterial contamination of ground garlic sold in the traditional market of Galang. The research method is descriptive to see the number of colonies and the characteristic of the types of bacteria that contaminate onions the white sold in the traditional market in Galang.. The result of laboratory samples obtanied 2 sample contaminated with Klebsiella oxytoca bacteria and 6 sample contaminated with Enterogenous aerogenosa bacteria. Conclutions obtained and the results of this study are ground garlic sample sold in the traditional market of galang distric. It can be concluded that 2 samples were polluted by Klebsiella oxytoca bacteria and 6 samples contaminated with aerogenous Enterobacter bacteria feasible consumption of larvae according to the regultions of BPOM no. HK.00.06.1.53.4011 of 2009 and Indonesian National Standart no.7338 of 2009 on herbs and spices the number of total plates is not greater and the threshold of 1x106 colony/gram